Legal Study of Unlawful Acts by The Opponents In Land Dispute Decision Number 6/Pdt.Bth/2024/Pn Bpp - Aldo Yanuarto; Aris Sunandar; Abdul Khair (JURNAL USM LAW REVIEW, 2025)
This study aims to conduct a juridical analysis of the elements and legal reasoning used by the panel of judges in establishing the existence of an unlawful act (onrechtmatige daad) committed by the Defendants in a land dispute case, as stipulated in the Decision of the Balikpapan District Court Number 6/PDT.BTH/2024/PN BPP. Employing normative legal research with a conceptual and case approach, this study focuses on the interpretation of Article 1365 of the Indonesian Civil Code (KUHPerdata) and the judicial construction applied by the court in assessing the Defendants’ actions. The urgency of this study lies in the increasing complexity of land disputes in Indonesia, which demand clearer doctrinal and judicial guidance in determining the threshold of unlawful acts in civil litigation. The novelty of this research is its integrative use of abuse of rights theory and good faith principles as analytical tools to assess the boundaries of civil liability, which have not been thoroughly explored in previous studies. The findings reveal that the Defendants' act of filing for execution over a parcel of land that had been lawfully transferred to the Plaintiff, without a legitimate legal basis, constitutes a clear instance of an unlawful act. Such conduct satisfies the juridical elements of tort as outlined in both doctrine and jurisprudence: the existence of an act, its unlawfulness, fault, actual damages, and a causal relationship between the act and the harm incurred. The court’s decision reflects a balanced consideration of good faith principles, legal protection doctrines, and the abuse of right theory in determining the Defendants’ civil liability. This study recommends a more consistent application of these doctrines to ensure legal certainty and justice in future land dispute adjudications.